2014
DOI: 10.1097/meg.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancers

Abstract: R0 resection in in-situ cancer has the best prognosis. Preventive cholecystectomy should be performed in high-risk patients (gallstones larger 3 cm; adenomatous polyps>1 cm; pancreatobiliary reflux, porcelain gallbladder, segmental adenomyomatosis, xanthogranulomatous cholecystitis). The histological stratification of gallbladder cancer should be carried out before starting further studies because squamous-cell carcinoma, adenocarcinoma, and papillary carcinoma are associated with different risk factors and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…This geographic variability is most likely attributable to differences in environmental exposures and a regional intrinsic predisposition to carcinogenesis [ 7 ]. This genetic predisposition is proposed to originate from population migration patterns in Central Asia/Himalayas through Bering Strait during the last glacial era [ 12 ]. However, though such patterns of prevalence are observed, there is no true unifying factor that explains this unusual geographic distribution.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This geographic variability is most likely attributable to differences in environmental exposures and a regional intrinsic predisposition to carcinogenesis [ 7 ]. This genetic predisposition is proposed to originate from population migration patterns in Central Asia/Himalayas through Bering Strait during the last glacial era [ 12 ]. However, though such patterns of prevalence are observed, there is no true unifying factor that explains this unusual geographic distribution.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Patients at high risk (stones >2-3 cm, associated polyps, nonfunctioning gallbladder, porcelain gallbladder, pancreaticobiliary reflux, segmental adenomyomatosis, and xanthogranulomatous cholecystitis) may significantly benefit from prophylactic cholecystectomy, particularly those in a high risk geographical location [ 3 , 12 ]. It is also recommended that gastrectomy patients undergo a concomitant cholecystectomy as these patients are predisposed to delayed gastric emptying with increased incidence of gallstones and rarely gallbladder cancers [ 12 ]. Potentially, unnecessary patient morbidity and the increased cost however remain barriers to this practice.…”
Section: Prognosismentioning
confidence: 99%
“…Cystic duct adenocarcinoma is a rare entity, and is considered a GB cancer [ 7 ]. Although the risk factors of GB cancer are being reported, those of cystic duct adenocarcinoma were reported nil [ 8 ]. Cystic duct adenocarcinoma is reported that it accounts for 8% of the entire GB cancer [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiologic studies, gallstones represent the most important risk factor for GbCa, being present in as many as 96% of patients [8]. Indeed, rates of GbCa increase with the prevalence of gallstone disease, which more commonly affects certain indigenous populations, particularly in North and South America.…”
Section: Environmental Risk Factors For Gallbladder Cancermentioning
confidence: 99%
“…Apart from gallstones, obesity, inflammation in bile ducts, typhoid, salmonella and, to a lesser extent, Helicobacter infections, chronic cholecystitis, gallbladder polyps and female gender are regarded as risk factors for GbCa (Table I) [8,[25][26][27][28][29]. Presence of chronic inflammation is considered as another predisposing factor for gallbladder malignancies.…”
Section: Environmental Risk Factors For Gallbladder Cancermentioning
confidence: 99%